2013
DOI: 10.3141/2396-04
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Heavy Vehicles on Freeway Operating Characteristics under Congested Conditions

Abstract: The significant impact of heavy vehicles (HVs) on freeway operations has been identified since the first edition of the Highway Capacity Manual (HCM). The HCM 2010 used passenger car equivalent (PCE) values and percentages of trucks, buses, and recreational vehicles to account for the effect of HVs on roadway performance. Unfortunately, the PCE values in the HCM 2010 relied on a limited field database and simulation runs that were calibrated for steady-flow traffic conditions, although the effect of HVs on tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…The distinctly longer headways the drivers of heavy semitrailer trucks kept from PCs compared with the short headways kept by their peers driving small semitrailer trucks. A possible explanation may be found in vehicle weights [39.6 kips, Class 8; 59.2 kips, Class 9 in a study referenced in Ahmed et al (26)]: longer headways related to heavier vehicle-braking distances.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The distinctly longer headways the drivers of heavy semitrailer trucks kept from PCs compared with the short headways kept by their peers driving small semitrailer trucks. A possible explanation may be found in vehicle weights [39.6 kips, Class 8; 59.2 kips, Class 9 in a study referenced in Ahmed et al (26)]: longer headways related to heavier vehicle-braking distances.…”
Section: Discussionmentioning
confidence: 99%
“…Vehicles were classified into three types by using the FHWA scheme of 13 vehicle classes (Table 1): motorcycles (Class 1), passenger cars (PC = Classes 2 and 3), light trucks (LT = Classes 4 to 7), and heavy trucks (HT = Classes 8 to 13). Average headways for (26).…”
Section: Freeway Pce Valuesmentioning
confidence: 99%
“…Heavy vehicles are known to have an impact on the traffic stream. Ahmed, Drakopoulos, and Ng (2013) found that headways between passenger cars increased due to the presence of heavy vehicles. They also found that the maximum throughput of the freeway decreased when the heavy vehicle percentage increased by more than 3 percent.…”
Section: Merging Freeway Designs and Their Safetymentioning
confidence: 99%
“…The other category of vehicles was the passenger car, which dominated the traffic stream. Ahmed et al (2013) conducted a study to determine the impact of Heavy Vehicles (HVs) on performance at different congestion levels. The study findings reveal that with an increase in the HVs percentage, the capacity and Level of Service (LoS) deteriorated.…”
Section: Introductionmentioning
confidence: 99%